Mitigasi Bencana Banjir dan Genangan Dalam Kawasan Perkembangan Permukiman di Kelurahan Berua, Kota Makassar - Andi Muh. Azzam Raihan Ramadhani; Wiwik Wahidah Osman; Abdul Rachman Rasyid (Jurnal Wilayah & Kota Maritim (Journal of Regional and Maritime City Studies), 2022)
Floods are caused by several things, such as the lack of water catchment areas or the presence of obstacles in drainage so that they are no longer able to accommodate rainwater capacity. Berua Village is one of the areas in Makassar City that often experiences flooding when the rainy season arrives, this is due to the rapid development of settlements, causing a lack of water catchment areas. This study aims to identify flood and inundation conditions based on the factors that cause flooding, identify surface water flows and drainage channels, and formulate flood and inundation disaster mitigation directives in settlements in the Berua Village. This research lasted for 5 months, starting from February to June 2021. This research used spatial, hydrological and descriptive analysis. Based on the results of this study, it is known that the surface runoff discharge is equal to 38.81 m3/second and there are 25 drainage channels that exceed the capacity. , making infiltration wells, and using the concept of rainwater harvesting, and non-structural mitigation, namely in the form of classifying disaster-prone groups and determining evacuation points.